The acquisition of derivational morphology a cross-linguistic perspective - Mattes, Veronika; Sommer-Lolei, Sabine; Korecky-Kröll, Katharina; Dressler, Wolfgang U., 1939- (Language acquisition & language disorders ;, 2021)
"This book offers the first systematic study of the early phases in the acquisition of derivational morphology from a cross-linguistic and typological perspective. It presents ten empirical longitudinal studies in genealogically and typologically diverse languages (Indo-European, Finno-Ugric, Altaic) with different degrees of derivational complexity. Data collection, analysis and systematic comparison between child speech and parental child-directed speech are strictly parallel across the chapters. In order to identify the productivity of a derivational pattern, signalling the crucial developmental stage in its acquisition, the concept of the mini-paradigm criterion was applied. Similar developmental processes can be observed in all children, independent of the language they acquire, but the children's courses of development also show obvious typological differences. This points towards an important impact of the structural properties of the specific language on emergence, use and the early course of development of derivational patterns"--